Cyclometalated ruthenium complexes with carboxylated ligands from a combined experimental/computational perspective. Issue 8 (31st January 2018) - Mydske Thoresen, Eirik; Balcells, David; Øien-Ødegaard, Sigurd; Hylland, Knut Tormodssønn; Tilset, Mats; Amedjkouh, Mohamed
Abstract : Nine new cyclometalated ruthenium(ii ) complexes have been developed, amongst which two have been examined by UV-Vis spectroscopy and TD-DFT to elucidate their potential as visible light photosensitizers. Abstract : The syntheses and characterization of nine new cyclometalated ruthenium complexes are reported. These structures consist of Ru(ii ) with bipyridine and phenylpyridine ligands which are substituted with ester or carboxylate groups. Two of the complexes were extensively studied and their properties were compared to those of two previously reported structures. The identities of the compounds were confirmed by NMR, HR-MS and single crystal XRD, and the electronic properties were investigated by UV-Vis spectroscopy. DFT and TD-DFT calculations showed that the intense absorbances in the visible region of the spectrum of these cyclometalated complexes are due to electronic excitations to virtual orbitals located on the carboxylated ligands. These results indicate that the compounds are promising candidates as sensitizers for more efficient photocatalysis with sunlight. Further, the carboxylate groups should facilitate their use as linkers in metal–organic frameworks.